CuxO/Cu based electrochemical sensor for the detection of CO2 gas. Issue 5 (20th October 2022) - Digvijay, B.; Amala, J.; Aravind, S. P.; Bhuvaneshwari, S.; Mohanraj, P.
ABSTRACT: Industrialization and urbanization have primarily contributed to air pollution, necessitating the need for the development of better sensing devices. Unlike other gases, Carbon dioxide (CO2 ) is more stable in the environment and poses a serious threat to the environment and health. Thus, the detection of CO2 gas becomes imperative. In the present work, a 3-electrode electrochemical cell was developed to detect CO2 gas. The working electrode (Cux O/Cu) was prepared by anodization of copper foil and the characterization studies has been done using XRD, SEM and FTIR techniques. The quantitative analysis of CO2 gas was performed by electrochemical techniques such as Cyclic Voltammetry (CV) and TAFEL. The potential window for CV was between −0.6 V to 1 V and −2 V to 1 V for NaCl and KCl electrolyte, respectively. The sensor developed has lower response time and could detect CO2 gas of concentrations upto 8000 ppm in both electrolytes. The sensor with KCl electrolyte showed a better response than NaCl, with a reduction current density of 0.016A. GRAPHICAL ABSTRACT: UF0001